Process of Minang’s Women Migration in Jakarta - Oktavi, Sinta; Sumarti, Titik (Sodality: Jurnal Sosiologi Pedesaan, 2015)
T h e p u rpo ses o f th is  s tu d y we re  to  a n a lyze th e m ig ra tio n  p ro cess  o f M in a n g ’s wo m en .  T h e  stu d y sh o w th a t (1 ) sin ce 1 9 80  M ina ng ’s wo m en  ten d  to  m igra te in  d irect wa y to  th e d est in a tio n  a rea  wh i ch  th ey h a ve  ch o o se a nd  in  th e ca se o f M in an g ’s wo m en  in  Ja ka rta  it’s m ea n  th a t th ey wen t to  Ja ka rt a  d irectly,  wh il e  transit trend in the other destination area  seldom practiced. The trend of direct migration pattern to Jakarta also supported by the improvement of the transportations facilities. Along with it, women migration flo w  b e co m es m o re o p en  sin ce  th e M in a n g ’s wo m en  m ig ra tio n  wa s ch a in  m ig ra tio n  ba sed o n  kin sh ip  wh o  have migrate first (2)Although Minang women migrant have stay in destination area for 5 (five) years or more,  they keep coming back to their origin area even once in a while.   K ey wo rd s: M in a n g ’s wo m en  m ig ra n ts,  pa tter n  an d  flo w o f m ig ra tion